2018
DOI: 10.1007/s13224-018-1124-6
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Applicability of Salivary Uric Acid Measurement in Preeclampsia and Normal Pregnancy and Its Correlation with Serum Uric Acid

Abstract: Purpose Hypertensive disorders complicate 5-10% of all pregnancies and contribute greatly to maternal morbidity and mortality. There are various biomarkers for detection of preeclampsia. Several studies have reported that positive correlation exists between serum uric acid (UA) levels and adverse maternal and fetal outcome. Significant advances have been made toward validation of salivary biomarkers. We conducted this study to determine levels of salivary UA and its correlation with serum UA normal pregnancy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…This time is sufficient for the release of saliva along with anti-oxidant molecules into the oral cavity and subsequent increase in the level of salivary UA. However, Greabu et al, (16) in their in vitro study and some others (4,20,21) reported significant reduction of UA in smokers. This difference may be due to the fact that saliva was evaluated in this study while the abovementioned studies evaluated the serum level of UA.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This time is sufficient for the release of saliva along with anti-oxidant molecules into the oral cavity and subsequent increase in the level of salivary UA. However, Greabu et al, (16) in their in vitro study and some others (4,20,21) reported significant reduction of UA in smokers. This difference may be due to the fact that saliva was evaluated in this study while the abovementioned studies evaluated the serum level of UA.…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, two solutions were mixed with the saliva, and the optical density was read at 500-530 nm (normal range is 3.6-8.2 mg/dL in males and 2.3-6.1 mg/dL in females). (16) The salivary level of amylase was measured by the kinetic photometric enzymatic technique.…”
Section: Methodsmentioning
confidence: 99%
“…Singh et al (2019) [ 33 ] observed a statistically significant correlation (r 2 = 0.690, p = 0.001) between saliva uric acid and serum uric acid of women diagnosed with pre-eclampsia. This study also observed a similar correlation between serum uric acid and salivary uric acid among all the three groups, i.e., severe pre-eclampsia (r = 0.827, p < 0.0001), non-severe pre-eclampsia (r = 0.818, p < 0.001), and pre-eclampsia (r = 0.920, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Singh et al recently found that salivary UA had a linear correlation with serum UA levels in women with preeclampsia. [ 19 ] However, their study was a cross-sectional study. The authors suggested that salivary UA levels could serve as an index for severity of preeclampsia and also provided a salivary UA cutoff value of 3.350 mg/dl which was predicted to be 78% sensitive and 73% specific.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that salivary UA levels could serve as an index for severity of preeclampsia and also provided a salivary UA cutoff value of 3.350 mg/dl which was predicted to be 78% sensitive and 73% specific. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%